Syntrophy between bacteria and archaea enhances methane production in an EGSB bioreactor fed by cheese whey wastewater - Domínguez-Espinosa, María Emperatriz; Cruz-Salomón, Abumalé; Ramírez de León, José Alberto; Hernández-Méndez, Jesús Mauricio Ernesto; Santiago-Martínez, Michel Geovanni (Frontiers in Sustainable Food Systems, 2023)
The cheese-making process generates large amounts of cheese whey wastewater (CWW), which is abundant in nutrients but difficult to dispose of, contributing to the eutrophication of natural environments due to inadequate waste management. Here we show the anaerobic digestion of CCW by syntrophy between bacteria and archaea in an expanded granular sludge bed (EGSB) bioreactor as a low-cost alternative for bioremediation and biofuel production. The performance of the EGSB bioreactor and the composition of the natural microbial community were evaluated. During the operation of the EGSB bioreactor, physicochemical parameters such as alkalinity ratio (0.25), pH (7.5), and temperature (26°C) were attained and maintained, as well as light- and oxygen-free conditions, which favored the metabolism of oxygen-sensitive bacteria and methane-producing archaea (methanogens). Under these conditions, the chemical oxygen demand (COD) removal rate was highly efficient (> 89%). Methane (CH4) was produced from organic matter degradation by a few methanogens, mainly from Methanosaeta spp., and was enhanced by the metabolic interaction between bacteria and archaea. The biochemical methane potential (BMP) was >335 mL CH4/gCOD, indicating that the syntrophic microbial community is very efficient in removing organic matter and CH4 produced from CWW. Our results suggest that CWW could be treated in EGSB bioreactors and used as a sustainable alternative to CH4 production and also provide insights for the design of synthetic microbial communities (SynComs) for bioremediation, biogas production, and other biotechnological processes.